Folding of a tandemly knotted protein: Evidence that a polypeptide chain can get out of deep kinetic traps. - Zhang, Hongyu; Jackson, Sophie E (Wiley, 2025)
It is hard to imagine how proteins can thread and form knots in their polypeptide chains, but they do. These topologically complex structures have challenged the traditional protein folding views of simple funnel-shaped energy landscapes. Previous experimental studies on the folding mechanisms of deeply knotted proteins with a single trefoil knot have yielded evidence that this topology has a more complicated folding landscape than other simpler proteins. However, to date, there have been no attempts to study the folding of any protein in which multiple threading events are needed to create more than one knot within a single polypeptide chain. Here, we report the construction and characterization of an artificial tandemly knotted protein. We find compelling evidence that both domains of the protein form trefoil knots with similar structures and stabilities to the parent single trefoil-knotted protein. In addition, we show that this tandemly knotted protein has a complex folding pathway in which there are additional very slow folding phases that we propose correspond to the formation of the second knot within the system. We also find evidence that during folding this protein gets transiently trapped in deep kinetic traps, however, the majority of protein chains (>90%) manage to partially unfold and acquire the native tandem-knot topology. This work highlights the fact that Nature can tolerate more complex protein topologies than we thought, and despite considerable misfolding during folding, protein chains can find their way to the native state even in the absence of molecular chaperones.
Publication status: Published
Keywords: fluorescence spectroscopy; folding kinetics; knotted protein; misfolding; protein folding; Protein Folding; Kinetics; Peptides; Models, Molecular; Proteins